Aggregation Operators of Interval‐Valued 2‐Tuple Linguistic Information. Issue 7 (5th February 2014) - Beg, Ismat; Rashid, Tabasam
<x xml:space="preserve">Abstract</x> The group decision‐making problem with linguistic information evaluation values of decision makers are used based on 2‐tuple interval‐valued. Operational laws on interval value 2‐tuple are introduced. On the basis of these laws, new aggregation operators are introduced by using the Choquet integral. A multiple attribute decision‐making method based on these aggregation operators is proposed. An example is given to illustrate the efficiency, practicality, and feasibility of our method.